Traditional Belief and Career Competence: Mediation Effects of Career Adaptability - Riskiyanti, Intan Yuli; Sunawan, Sunawan; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2022)
Career competencies urge to be prepared since the beginning of adolescence since most of students’ career fails because of it. Regarding this reason, the present study attempted to prove that career adaptability can mediate the relationship between traditional belief and students’ career competencies. This correlational study involved 368 students from four senior high school in Wirosari Sub-district, Grobogan Regency, Central Java. Findings showed traditional belief positively predicted students’ career adaptability and career competencies, career adaptability positively predicted students’ career competencies, and traditional belief boosted students’ career competencies through career adaptability. According to these results, it is important to consider traditional belief to improve career adaptability and students’ career competencies.